A Case of Complete Renal Duplex with H-Shaped Ureter. (7th June 2012) - Ghobashy, A.; El-Shazly, M.; Lari, A.; Al-Hunaidy, O.; Allam, A.; Alenezy, N.; Yordanov, E.; Hathout, B.
Abstract : We present a case of complete renal duplex with H-shaped double ureter opening into the bladder with 2 separate orifices. It is an extremely rare variety of renal duplex which was reported only once in the literature. Fifty-four-year-old male presented to our department with right renal pain. Noncontrast CT revealed stone midthird right ureter with duplex right kidney. Retrograde ureteropyelography and ureteroscopy revealed this rare anomaly.